Integrasi Nilai Padungku dalam Konseling Analisis Transaksional untuk Meningkatkan Keterampilan Interaksi Sosial Siswa - Sirumpa, Yuyun Lestari; Ratu, Bau; Nurwahyuni, Nurwahyuni; Fitirani, Dian; Arifyadi, Azam; Puswiartika, Dhevy; Lakadjo, Mohamad Awal (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
This study explores the meaningfulness of group counseling based on Transactional Analysis (TA) integrated with Padungku cultural values in enhancing students' social interaction skills. The research employed a Classroom Action Research (CAR) design using the Hopkins model over two cycles. Participants were 10 tenth-grade students selected through purposive sampling. Data were collected through a social interaction skills instrument, process observations, and student evaluations of counseling services. Results indicated significant improvement, with students progressively shifting from "Low" to "Very High" categories of social interaction. Observations supported the quantitative data, showing increased participation, communication, and self-control, while student evaluations revealed positive perceptions of the intervention's meaningfulness. The discussion links these changes to the ego state mechanism in TA and reinforcement of local cultural values. The study concludes that this integrative approach is meaningful in developing culturally responsive school counseling practices.